Neighbourhood Life Chances. Local Strategies of Needs Fulfilment and Individual Resources - Schuster, Nina; Volkmann, Anne (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
In order to capture individual life chances and their spatial relations, the paper expands the neighbourhood effects research by referring to the capability approach. We conceptualise life chances as the opportunities and freedom to fulfil human needs, which is determined by individual resources. The opportunities and freedoms depend on the life circumstances and underly profound changes during life course, with corresponding changes of the neighbourhoods’ significance for life chances. Instead of “disadvantaged neighbourhoods” we focus on disadvantaged life circumstances in neighbourhoods.
Keywords: Neighbourhood effects; Socio-spatial disadvantages; Life chances; Resources; Needs